2023
DOI: 10.1021/acsabm.3c00506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PEGylation on WS2 Nanosheets and Its Application in Photothermal Therapy

Rohan Bahadur,
Barkha Singh,
Deepika Rai
et al.

Abstract: Photothermal therapy (PTT) is an alternative cancer therapy with minimal side effects and higher efficiency and selectivity. In this study, WS 2 nanosheets were developed by ultrasonic exfoliation with different ratios of polyethylene glycol (PEG), and their effects on physicochemical properties were studied. The utilization of PEG during sonication significantly influenced the size and thickness of the resulting WS 2 nanosheet layers, which was confirmed through scanning electron microscopy, atomic force micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Bahadur et al demonstrated that WS 2 nanosheets, when functionalized with polyethylene glycol (PEG), exhibited enhanced dispersibility in aqueous solutions. This enhanced hydrophilicity improved their biocompatibility and enhanced the efficacy in the ablation of MDAMB-231 breast cancer cells . The biocompatibility of the borophene/zinc oxide (BZ) nanocomposite demonstrated nontoxic behavior and effective bactericidal properties against both Gram-positive and Gram-negative bacteria.…”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 99%
“…Bahadur et al demonstrated that WS 2 nanosheets, when functionalized with polyethylene glycol (PEG), exhibited enhanced dispersibility in aqueous solutions. This enhanced hydrophilicity improved their biocompatibility and enhanced the efficacy in the ablation of MDAMB-231 breast cancer cells . The biocompatibility of the borophene/zinc oxide (BZ) nanocomposite demonstrated nontoxic behavior and effective bactericidal properties against both Gram-positive and Gram-negative bacteria.…”
Section: Properties Of 2d Nanomaterials Used In Healthcare Applicationsmentioning
confidence: 99%
“…MXenes. [3] MXenes (pronounced "Maxeens"), are a new class of materials made from carbides, nitrides, and carbonitrides of transition metals. They were first discovered due to their structural similarities to graphene, and since then, their development has progressed rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…This has led researchers to investigate other materials, such as Porous carbons, [ 1,2 ] Transition metal dichalcogenides (TMDCs), and MXenes. [ 3 ] MXenes (pronounced “Max‐eens”), are a new class of materials made from carbides, nitrides, and carbonitrides of transition metals. They were first discovered due to their structural similarities to graphene, and since then, their development has progressed rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…These nanomaterials are also known as photothermal therapy agents (PTAs). In the past decade, transition metal dichalcogenide (TMDC) nanomaterials including MoS 2 , WS 2 , MoSe 2 , WSe 2 , , and MoTe 2 have been widely researched as promising PTAs owing to their high absorbance of NIR light, high specific surface-to-volume ratio, and easy surface functionalization, which make them not only good PTAs but also drug carriers for synergistic therapy. However, TMDC nanomaterials need to be surface functionalized with biocompatible polymers to improve their physiological stability and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…One way to attach biocompatible polymers is by using van der Waals forces. For example, soybean phospholipid, chitosan, poly­(ethylene glycol) (PEG), polyvinyl­pyrrolidone, polyethylenimine (PEI), and F-127 were attached to TMDC nanomaterials via van der Waals forces. ,,, , Another way to conjugate TMDC nanomaterials with biocompatible polymers is through chemical bonds. TMDC nanomaterials can be conjugated with the polymers terminated with lipoic acid groups such as LA-PEG and LA-PEI by forming metal–sulfur bonds. ,, All of these methods require hours or even days of stirring of nanomaterials and biocompatible polymers together.…”
Section: Introductionmentioning
confidence: 99%